INVESTMENT POLICY, GEOPOLITICAL RISK AND THE ROLE OF INSTITUTIONS: INTERNATIONAL EVIDENCE - Tekin, Hasan (Bank Indonesia, 2024)
In today’s world, given the increasing importance of geopolitical risk (GPR), this study investigates the impact of GPR on corporate investment, or capital expenditure, of nonfinancial firms considering institutional settings. Utilising data on 337,399 firm-years from 42 countries for the period 1996-2021 (retrieved from Datastream), empirical findings show that firms in higher GPR countries present fewer investment opportunities. Namely, firms use capital expenditures as a substitute for GPR. Next, the negative impact of governance on capital expenditures across the whole sample remains for the firms in civil law countries. However, it reverts to positive for those in common law countries. In other words, capital expenditures are a substitute for (outcome of) governance in civil (common) law countries.Overall, investors should be concerned about the level of GPR, governance, and legal system when determining where to invest. Policymakers should consider GPR and institutional quality to attract foreign investors.